Impact of Functionalization and Co-Additives on Dioxazolone Electrolyte Additives. Issue 8 (25th May 2020) - Gauthier, Roby; Hall, David S.; Lin, Katherine; Baltazar, Jazmin; Hynes, Toren; Dahn, J. R.
Abstract : Finding new electrolyte additives could help create lithium-ion batteries with better performance at high voltage, allowing higher energy density. However, finding the perfect additive remains a tremendous challenge, since researchers still don't understand how to predict their performance. A new group of dioxazolone electrolyte additives have been tested in lithium-ion batteries alone or in combination with well-known co-additives. The new additives consist of a 3-phenyl-1, 4, 2-dioxazol-5-one (PDO) parent structure with or without (methoxy, fluoro and nitro) functional groups on the para position of the phenyl ring. It is found that PDO (no functional group) and p -(4-nitrophenyl)-1, 4, 2-dioxazol-5-one (pNDO) are the best performing dioxazolones overall and show promising results.